Data on physicochemical properties of active films derived from plantain flour/PCL blends developed under reactive extrusion conditions - Gutiérrez Carmona, Tomy José (2017)
The data given below relates to the research paper entitled: “Eco-friendly films prepared from plantain flour/PCL blends under reactive extrusion conditions using zirconium octanoate as a catalyst”, recently published by our research group. This article provides information concerning the physicochemical properties of the above-mentioned film systems: thickness, density, opacity, moisture content and surface moisture.